Circulating microRNAs differentiate Kawasaki Disease from infectious febrile illnesses in childhood. (September 2020) - Jone, Pei-Ni; Korst, Armin; Karimpour-Fard, Anis; Thomas, Thomas; Dominguez, Samuel R.; Heizer, Heather; Anderson, Marsha S.; Glode, Mary P.; Sucharov, Carmen C.; Miyamoto, Shelley D.
Abstract: Background: Kawasaki Disease (KD) is an acute vasculitis of unknown etiology in children that can lead to coronary artery lesions (CAL) in 25% of untreated patients. There is currently no diagnostic test for KD, and the clinical presentation is often difficult to differentiate from other febrile childhood illnesses. Circulating microRNAs (miRNAs) are small noncoding RNA molecules that control gene expression by inducing transcript degradation or by blocking translation. We hypothesize that the expression of circulating miRNAs will differentiate KD from non-KD febrile illnesses in children. Methods: Circulating miRNA profiles from 84 KD patients and 29 non-KD febrile controls (7 viral and 22 bacterial infections) were evaluated. 3 ul of serum from each subject was submitted to 3 freeze/heat cycles to ensure miRNA release from microvesicles or interaction with serum proteins. miRNAs were reverse transcribed using a pool of primers specific for each miRNA. Real-time PCR reactions were performed in a 384 well plate containing sequence-specific primers and TaqMan probes in the ABI7900. '. Results: KD patients (3.6 ± 2.2 yrs., 58% male) were found to have a unique circulating miRNA profile, including upregulation of miRNA-210-3p, −184, and -19a-3p ( p < .0001), compared to non-KD febrile controls (8.5 ± 6.1 yrs., 72% male). Conclusions: Circulating miRNAs can differentiate KD from infectious febrile childhood diseases, supporting their potential as a diagnostic biomarker for KD. Graphical abstract: Unlabelled Image Highlights: Circulating miRNAs differentiate Kawasaki Disease from febrile childhood diseases. Circulating miRNAs serve as a potential diagnostic biomarker for Kawasaki Disease. Circulating miRNAs could lead to earlier treatment of incomplete Kawasaki Disease.